DEFINITIONS AND THEORIES OF PUBLIC SPACE (City: History, Culture, Society, 2020)
The part of the book ‘Order in the Streets. The Political History of Warsaw’s Public Space in the First Half of the 19th Century’Detailed information is here https://storage.googleapis.com/flyers.peterlang.com/March_2020/978-3-631-80070-6_normal_English.pdf
Keywords: Public space; Warsaw; Russian empire; XIX century